2015
DOI: 10.1111/hex.12353
|View full text |Cite
|
Sign up to set email alerts
|

Service user involvement in mental health care: an evolutionary concept analysis

Abstract: Background The concept of service user involvement is an evolving concept in the mental health-care literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 77 publications
(168 reference statements)
3
69
0
9
Order By: Relevance
“…There is a growing body of evidence for the benefits of involving service users and carers in the design and delivery of mental health services at both a systems and individual level. PPI has been shown to change services for the better through enhanced performance, increased accountability and enhanced person‐centred care . At an individual level, reductions in symptom severity, positive impacts on personal recovery, individual rights, mental health literacy, confidence, hope and empowerment are all associated with increased involvement in mental health services .…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence for the benefits of involving service users and carers in the design and delivery of mental health services at both a systems and individual level. PPI has been shown to change services for the better through enhanced performance, increased accountability and enhanced person‐centred care . At an individual level, reductions in symptom severity, positive impacts on personal recovery, individual rights, mental health literacy, confidence, hope and empowerment are all associated with increased involvement in mental health services .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated how health professionals experience user involvement at an individual level and how they work to enhance involvement, such as within mental health, cancer, diabetes and coronary care (Millar, Chambers, & Giles, 2016; Snyder & Engström, 2016). Findings have shown that the main motive for health professionals to initiate user involvement is to gain access to user knowledge as an alternative to professional knowledge or as support for professional knowledge (Sahlsten, Larsson, Sjöström, & Plos, 2009; Solbjør & Steinsbekk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As proven for nurses (Cahill, 1998;Henderson, 2003) and physicians (Froschet et al, 2012), taking up this new, collaborative role poses a challenge, but is a necessity to facilitate patient participation (Larsson et al, 2011). Healthcare workers have to be able or willing to share their responsibilities and power with their patients before participation can actually take place (Millar et al 2015). Patient participation is a reciprocal process where healthcare workers and patients act upon each other's behavior (Longtin et al, 2010), and the patient initially depends on the healthcare worker's willingness to collaborate.…”
Section: Introductionmentioning
confidence: 99%